Agency, signals, and the paradox of efficiency: Mediating role of investment efficiency in determining firm value in Indonesia - Wicaksana, Ketut Arya Bayu; Purbawangsa, Ida Bagus Anom; Artini, Luh Gede Sri; Candraningrat, Ica Rika (Edelweiss Applied Science and Technology, 2025)
This study examines the mediating role of investment efficiency in the relationship between financial performance, business risk, institutional ownership, and board diversity on firm value in Indonesia. Grounded in agency and signaling theories, the study employs a dual-theoretical framework to analyze how internal governance mechanisms affect market valuation. Using panel data from 711 firm-year observations of non-financial firms listed on the Indonesia Stock Exchange (2016–2019), the analysis is conducted using PLS-SEM. Contrary to expectations, financial performance and investment efficiency significantly and negatively affect firm value, suggesting that conservative financial behavior may signal limited growth prospects. Business risk also has a negative impact on firm value but shows a significant partial mediation through investment efficiency. Institutional ownership positively influences investment efficiency but does not directly affect firm value. Board diversity negatively correlates with firm value and has no significant impact on investment efficiency. The findings highlight a disconnect between internal governance and market perception, particularly in emerging markets where speculative growth expectations may overshadow governance signals. This study contributes to the literature by revealing the context-dependent nature of agency mechanisms and signaling effects and emphasizes the importance of aligning internal strategies with external communication to reduce perceptual gaps.